Training-of-trainers: A strategy to build country capacity for SLMTA expansion and sustainability - Maruta, Talkmore (Afr J Lab Med, 2014)
BACKGROUND: The Strengthening Laboratory Management Toward Accreditation (SLMTA) programme uses a training-of-trainers (TOT) model to build capacity for programme scale-up. The TOT strategy is designed to maximise utilisation of its graduates whilst minimising inconsistencies and ensuring high programme quality during global expansion. OBJECTIVES: To describe the SLMTA TOT programme approach. METHODS: The two-week training, led by carefully selected and trained master trainers, enables effective and authentic implementation of the curriculum by its graduates. The teachback methodology used allows participants to practise teaching the curriculum whilst learning its content. A trainer’s toolkit provides all the materials necessary for teaching and must be followed faithfully during training. Two surveys were conducted to assess the effectiveness of the TOT strategy: one sent to 316 TOT graduates in 25 countries and the other sent to the programme leaders in 10 countries. RESULTS: By the end of 2013, 433 SLMTA trainers had been trained who, in turn, taught more than 1900 people to implement SLMTA in 617 laboratories in 47 countries. Ninety-seven percent of the 433 TOT graduates and 87% of the 38 master trainers are based in developing countries. Ninety-two per cent of the graduates have been utilised at least once in programme implementation and, as of August 2013, 87% of them were still actively involved in programme activities. Ninety-seven per cent of the graduates stated that the TOT workshop prepared them well for training or other programme tasks. CONCLUSION: The SLMTA TOT strategy is effective in building local capacity for global programme expansion whilst maintaining programme quality.